GREEN SYNTHESIS OF HALOGEN SUBSTITUTED CHALCONE AGAINST CERVICAL CANCER (HeLa) CELL LINES - Fikroh, Retno Aliyatul; Matsjeh, Sabirin; Anwar, Chairil; Nurohmah, Beta Achromi (INSECTA: Integrative Science Education and Teaching Activity Journal, 2023)
Cervical cancer is the second leading cause of death in women. Many cancer treatments currently provide toxic effects on normal cells. Therefore, alternative treatment using chalcone derivatives has potent anticancer properties that can help reduce cancer side effects. Chalcone derivatives with halogen and methoxy groups in ring B can potentially inhibit cancer cells. This research aimed to synthesize halogen-substituted chalcone by a green chemistry approach and determine activity against cervical cancer (HeLa) cell lines. The Claisen-Schmidt reaction was used to synthesize 2'-hydroxy-2-bromo-4,5-dimethoxychalcone using a grinding technique. The purity of the synthesized compound was determined using thin-layer chromatography and melting range. The compounds' structures were characterized using FTIR, MS 1H, and 13C-NMR. The result showed that the synthesized compound was yielded in 53% as a yellow solid. In vitro cytotoxicity of the synthesized chalcone was evaluated by the MTT assay method. The IC50 of the compound was 67,23 μg/mL as a moderate activity inhibiting cervical cancer (HeLa) cell lines. Based on the IC50 value, this compound can be a candidate for anticancer against Cervical cancer (HeLa) cell lines.